Anatomical Assessment of the Adult Skeleton of Zebrafish Reared Under Different Thyroid Hormone Profiles. Issue 10 (29th April 2019) - Keer, Stephanie; Cohen, Karly; May, Catherine; Hu, Yinan; McMenamin, Sarah; Hernandez, Luz Patricia
ABSTRACT: Thyroid hormone (TH) directs the growth and maintenance of tissues throughout the body during development and into adulthood, and plays a particularly important role in proper ossification and homeostasis of the skeleton. To better understand the roles of TH in the skeletogenesis of a vertebrate model, and to define areas of the skeleton that are particularly sensitive to developmental TH, we examined the effects of hypo‐ and hyperthyroidism on skeletal development in zebrafish. Performing a bone‐by‐bone anatomical assessment on the entire skeleton of adult fish, we found that TH is required for proper ossification, growth, morphogenesis, and fusion of numerous bones. We showed that the pectoral girdle, dermatocranium, Weberian apparatus, and dentary are particularly sensitive to TH, and that TH affects development of skeletal element regardless of bone type and developmental origin. Indeed, the hormone does not universally promote ossification: we found that developmental TH prevents ectopic ossification in multiple thin bones and within connective tissue of the jaw. In all, we found that TH regulates proper morphogenesis and ossification in the majority of zebrafish bones, and that the requirement for the hormone extends across bone types and developmental profiles. Anat Rec, 302:1754–1769, 2019. © 2019 American Association for Anatomy